2022
DOI: 10.1017/ice.2022.108
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) between hospital workers and members of their household: Nationwide, registry-based, cohort study from Norway

Abstract: Background: Understanding and limiting infection in healthcare workers (HCWs) and subsequent transmission to their families is always important and has been underscored during the COVID-19 pandemic. Except in specific and local settings, little is known about the extent of such transmissions at the national level. Objective: To describe SARS-CoV-2 infection in HCWs and to estimate the risk of HCWs transmitting COVID-19 to their household members, including calculating the secondary attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…When considering potential risk factors of SARS-CoV-2 infection among HCWs in our study, we did not find a significant difference in the infection rates among HCWs working in wards involved and not involved in the treatment of COVID-19 patients, clinical or non-clinical areas, or across different wards and these findings applied to both phases of the study. Our findings are in contrast to some previous studies, especially those studies performed during the early pandemic stage 22 , which reported higher infection rates among HCWs working in COVID-19 wards with direct patient contact, but our findings are in line with the emerging literature pointing out that, except for breaches in PPE, the main risks to HCWs come from outside of work factors (in the community and household) 17,[23][24][25][26] . In our cohort, before implementation of the vaccination programme (study phase 1), nurses had the highest adjusted likelihood of being infected, while physicians had a lower likelihood.…”
Section: Discussionsupporting
confidence: 54%
“…When considering potential risk factors of SARS-CoV-2 infection among HCWs in our study, we did not find a significant difference in the infection rates among HCWs working in wards involved and not involved in the treatment of COVID-19 patients, clinical or non-clinical areas, or across different wards and these findings applied to both phases of the study. Our findings are in contrast to some previous studies, especially those studies performed during the early pandemic stage 22 , which reported higher infection rates among HCWs working in COVID-19 wards with direct patient contact, but our findings are in line with the emerging literature pointing out that, except for breaches in PPE, the main risks to HCWs come from outside of work factors (in the community and household) 17,[23][24][25][26] . In our cohort, before implementation of the vaccination programme (study phase 1), nurses had the highest adjusted likelihood of being infected, while physicians had a lower likelihood.…”
Section: Discussionsupporting
confidence: 54%
“…When considering potential risk factors of SARS-CoV-2 infection among HCWs in our study, we did not nd a signi cant difference in the infection rates among HCWs working in wards involved and not involved in the treatment of COVID-19 patients, clinical or non-clinical areas, or across different wards and these ndings applied to both phases of the study. Our ndings are in contrast to some previous studies, especially those studies performed during the early pandemic stage 22 , which reported higher infection rates among HCWs working in COVID-19 wards with direct patient contact, but our ndings are in line with the emerging literature pointing out that, except for breaches in PPE, the main risks to HCWs come from outside of work factors (in the community and household) 17,[23][24][25][26] . In our cohort, before implementation of the vaccination programme (study phase 1), nurses had the highest adjusted likelihood of being infected, while physicians had a lower likelihood.…”
Section: Discussionsupporting
confidence: 51%
“…Secondary attack rate (SAR) is a good measure of SARS-Cov2 transmission, providing a full picture of both the protection against getting infected and the diminution of the contagiousness that the immunity may confer. Apart from the immunity of the population and the VoC considered, SAR is known to vary greatly by contact settings, ranging from 20% in households to 6% in social gatherings during the first year of the pandemic [23][24][25][26] , but also by the symptoms of the index cases 27,28 and the socio-demographic characteristics of the studied population 26,[28][29][30][31] . By definition, SAR also depends directly on the capacity to detect SARS-CoV-2 infections among contacts, which includes the propensity of the contacts to get tested.…”
Section: Introductionmentioning
confidence: 99%